Comparison of computed tomography findings between odontogenic keratocyst and ameloblastoma in the mandible: Criteria for differential diagnosis. Issue 1 (January 2023) - Kaneko, Naoki; Sameshima, Junsei; Kawano, Shintaro; Chikui, Toru; Mitsuyasu, Takeshi; Chen, Hu; Sakamoto, Taiki; Nakamura, Seiji
Abstract: Objectives: Appropriate differential diagnosis between odontogenic keratocysts (OKCs) and ameloblastomas before treatment is crucial, but the radiographic findings, including computed tomography (CT), are often similar. This study, therefore, aimed to compare the CT findings of OKCs and ameloblastomas in the mandible. Methods: Forty-one OKC and 28 ameloblastoma patients were radiologically evaluated by using initial CT images focusing on features such as long/short diameters, CT values, the appearance of the cortex, locularity, scalloped margins, sclerotic rims, and high-density structures. Subtypes of ameloblastoma were also considered. Statistical analyses, including multivariate logistic regression analysis, were performed to determine the features that were helpful for differential diagnosis. Results: Short diameters and locularity were found to be significant features in the differential diagnosis. Between unicystic and conventional ameloblastomas, the frequency of sclerotic rims and buccal disappearance was significantly different. Based on these results, criteria were established for differential diagnosis between OKCs and ameloblastomas, and the diagnostic accuracy was 92.8 %. Conclusion: This finding indicates that several CT findings are strikingly different between OKCs and ameloblastomas, and that these criteria for differential diagnosis are clinically useful.